Oral Diseases and Oral Health–Related Quality of Life among Kenyan Children and Adolescents with HIV. (April 2023) - Wang, Y.; Ramos-Gomez, F.; Kemoli, A.M.; John-Stewart, G.; Wamalwa, D.; Benki-Nugent, S.; Slyker, J.; Seminario, A.L.
Introduction: Children and adolescents living with HIV (CALHIV) have a higher risk of hard and soft oral tissue diseases as compared with their healthy peers. It is important to increase awareness regarding the need to integrate oral health within medical care among pediatric HIV populations. Studies on associations of oral diseases with oral health–related quality of life (OHRQoL) in CALHIV are lacking. This study examined the association between oral diseases and OHRQoL in Kenyan CALHIV. Methods: This cross-sectional analysis was nested in a longitudinal cohort study of CALHIV in Nairobi. CALHIV received oral examinations, and the World Health Organization's Oral Health Surveys and Record Form was administered. OHRQoL was measured with the Parental-Caregiver Perceptions Questionnaire, with the subdomains of global, oral symptoms, function limitations, and emotional and social well-being, with higher scores indicating poorer OHRQoL. Linear regression was used to model associations between OHRQoL and oral diseases, adjusting for age at the time of oral examination, CD4 counts, and caregiver's education. Results: Among 71 CALHIV, the mean age was 12.6 y (SD, 2.9; range, 10 to <21), and the mean composite OHRQoL score was 12.6 (SD, 11.2). Ulcers (not herpes simplex virus or aphthous) were associated with the worst overall OHRQoL (mean, 21.8; SD, 11.1;P = 0.055) and oral symptoms subdomain (mean, 7.0, SD, 2.5;P = 0.003). Children with dry mouth and untreated caries had significantly higher mean global OHRQoL scores than those without disease (P < 0.0001). In the multivariate analysis, the OHRQoL composite score was 6.3 units (95% CI, –0.3 to 12.9) higher for those who had dry mouth and untreated dental caries; dry mouth accounted for the highest percentage of variability of OHRQoL (9.6%) and the global subdomain (31.9%). Ulcers accounted for the highest percentage of variability of the oral symptoms domain (15.4%). Conclusions: Oral ulcers, dry mouth, and untreated caries were associated with poorer OHRQoL in CALHIV. Integrating oral health into the primary care of CALHIV may improve their OHRQoL. Knowledge Transfer Statement: This study aimed to determine the association of oral diseases with the oral health–related quality of life of children and adolescents living with HIV (CALHIV). The findings will form part of the evidence to incorporate oral health protocols into care programs for CALHIV. Oral health monitoring has the potential to increase the surveillance of HIV clinical status, monitor the effectiveness of antiretroviral therapy, and improve the oral health–related quality of life of CALHIV.